2022
DOI: 10.1080/0886022x.2022.2079522
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics improve renal function, glucose, lipids, inflammation and oxidative stress in diabetic kidney disease: a systematic review and meta-analysis

Abstract: Aims The role of probiotics in the management of diabetic kidney disease (DKD) has been shown. Several current trials are investigating the effect of probiotics, which are widely used to modulate biomarkers of renal function, glucose, lipids, inflammation and oxidative stress in patients with DKD. However, their findings are controversial. This study aimed to systematically evaluate the impact of probiotics on patients with DKD via meta-analysis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 44 publications
(113 reference statements)
2
29
0
1
Order By: Relevance
“…This, coupled with the low number of trials per marker, made the single study that reported significant benefits on serum Cr, BUN, Cys-C, and urine total protein [ 69 ] a large influence on the overall pooled results. In an earlier review, Wang et al [ 70 ] reached similar conclusions to Dai et al [ 34 ], where the team reported that probiotics were beneficial in improving renal function in DN patients by increasing eGFR and decreasing both serum Cr and BUN; however, this contrasts with the previously described findings of Tarrahi et al [ 68 ] concerning eGFR and BUN. Less recent reviews [ 71 , 72 ] included fewer trials and did not show promise with respect to any renal biomarker, likely owing to smaller sample sizes.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This, coupled with the low number of trials per marker, made the single study that reported significant benefits on serum Cr, BUN, Cys-C, and urine total protein [ 69 ] a large influence on the overall pooled results. In an earlier review, Wang et al [ 70 ] reached similar conclusions to Dai et al [ 34 ], where the team reported that probiotics were beneficial in improving renal function in DN patients by increasing eGFR and decreasing both serum Cr and BUN; however, this contrasts with the previously described findings of Tarrahi et al [ 68 ] concerning eGFR and BUN. Less recent reviews [ 71 , 72 ] included fewer trials and did not show promise with respect to any renal biomarker, likely owing to smaller sample sizes.…”
Section: Discussionmentioning
confidence: 60%
“…Similar results were found by Tarrahi et al [ 68 ] from their analysis of seven trials administering probiotics in DN patients, revealing significant changes of −0.18 mg/dL (95% CI: −0.26; −0.09) in serum Cr, but no change in BUN or GFR. Contrarily, in their recent meta-analysis of DKD patients, Dai et al [ 34 ] reported that probiotics improved multiple biomarkers of renal injury, including serum Cr, BUN, Cys-C, the Alb/Cr ratio, and sodium, but this analysis stemmed from the exclusion of a study of elderly DN patients by [ 69 ] due to language-based exclusion criteria. This, coupled with the low number of trials per marker, made the single study that reported significant benefits on serum Cr, BUN, Cys-C, and urine total protein [ 69 ] a large influence on the overall pooled results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain therapeutic methods might alter the composition of the gut microbiota and promote the treatment of nephrotoxicity induced by cyclosporine (Figure 2). Altering the gut microbiota by using probiotics can delay the progression of renal injury and reduce inflammation and/or oxidative stress [30]. For example, the administration of Lactobacillus plantarum can decrease the risk of developing a gut-mediated condition in children undergoing HSCT [31].…”
Section: Probiotics As Therapeutic Agents Against Gvhd In Hsctmentioning
confidence: 99%
“…Based on the reports mentioned above, although increasing evidence has suggested that dysregulated autophagy in glomerular and tubular cells is strongly associated with the pathogenesis of DKD, the exact mechanism of autophagy remains to be elucidated. An increasing number of studies have shown that there is an interplay between inflammation, oxidative stress, and autophagy which play an important role in DKD [ 24 , 25 ]. Autophagy as an evolutionarily conserved cellular process protects renal cells from damage by inhibiting oxidative stress and inflammation in DKD [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%